Tin incorporated periodic mesoporous organosilicas (Sn-PMOs): synthesis, characterization, and catalytic activity in the epoxidation reaction of olefins - Sisodiya, Sheetal; Shylesh, S.; Singh, A. P. (Catalysis Communications, 2011)
Tin incorporated mesoporous organosilicas (Sn-PMO) having uniform hexagonal arrangements were prepared using alkyl trimethylammonium bromide surfactants under basic reaction conditions. Characterization techniques revealed that the structural ordering, morphology, and the percentage of tin incorporation depend critically on the hydrophobic chain length of surfactants. The Sn-PMO samples are thermally stable up to 500 degrees C under air atmosphere and were hydrothermally stable up to 100 h in boiling water. The organotinsilicates showed excellent catalytic activity and reusability in the epoxidation of norbornene and ciscyclooctene than an Sn-MCM-41 due to organic groups in the frame wall positions and the better accessibility of reactants to the active sites. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: epoxidation; Hydrothermal stability; Mesoporous; Organosilica; Sn-MCM-41; Sn-PMO